Right Coronary Artery Ectasia Manifesting With Acute Coronary Syndrome and Atrial Fibrillation: A Case Report - Toluwalase Awoyemi; Tim Provias (Annals of Internal Medicine: Clinical Cases)
The patient is a 59-year-old man who presented with substernal chest pain. Electrocardiogram showed evidence of inferior ST-segment elevation, and his troponin I level peaked at 40 µg/L. Coronary angiogram showed a severely ectatic right coronary artery with near-total acute thrombotic occlusion of the distal right coronary artery and total acute thrombotic occlusion of the distal posterior descending artery. He had a successful intravascular ultrasound-guided aspiration thrombectomy with a penumbra and intracoronary tissue plasminogen activator infusion. This case highlights an alternative way of treating acute thrombotic occlusion of ectatic arteries asides from the conventional but challenging practice of coronary revascularization with stent placement.